We can’t change it Until We Face it: A Counternarrative for Racial Justice - Dianne Ramdeholl (Adult Education Research Conference, 2023)
This paper extends on a recent book I co-authored which documented struggles of racialized faculty in academia. This autoethnography offers further observations about racism in academia.
Keywords: critical race theory; adult education